Alisporivir with peginterferon/ribavirin in patients with chronic hepatitis C genotype 1 infection who failed to respond to or relapsed after prior interferon‐based therapy: FUNDAMENTAL, a Phase II trial. Issue 7 (21st November 2014) - Buti, M.; Flisiak, R.; Kao, J.‐H.; Chuang, W.‐L.; Streinu‐Cercel, A.; Tabak, F.; Calistru, P.; Goeser, T.; Rasenack, J.; Horban, A.; Davis, G. L.; Alberti, A.; et al.
Summary Alisporivir (ALV) is an oral, investigational host‐targeting agent, with pangenotypic activity against hepatitis C virus (HCV). This randomized, double‐blind, placebo‐controlled, Phase II study explored the efficacy and safety of ALV with peginterferon‐α2a/ribavirin (PR) in patients with chronic HCV genotype 1 infection in whom prior PR had failed (43% relapsers, 34% null responders and 23% partial responders). Four‐hundred‐and‐fifty‐nine patients were randomized (1:1:1:1) to ALV 600 mg once daily (QD), ALV 800 mg QD, ALV 400 twice daily (BID) or placebo plus PR for 48 weeks. When the global ALV trial programme was put on clinical hold, all patients in this study had received ≥31 weeks of randomized treatment; patients completed 48 weeks on PR alone. All ALV groups demonstrated superior rates of complete early virologic response (cEVR; primary endpoint) vs PR alone (P ≤ 0.0131), with highest cEVR rate seen with ALV 400 mg BID (74% vs 36% with PR alone; P < 0.0001). Respective SVR12 rates (key secondary endpoint) were 65% vs 26% in prior relapsers, 63% vs 5% in partial responders and 68% vs 3% in null responders. In patients who received >40 weeks of randomized treatment, the SVR12 rate was 89% for ALV 400 mg BID vs 30% for PR alone (P = 0.0053). Rates of viral breakthrough and relapse were lowest with ALV 400 mg BID. One case of pancreatitis (fully recovered) occurred with ALV/PR. Common AEs were headache, fatigue, anaemia, neutropenia and nausea. Hypertension was infrequent, but more common with ALV. ALV merits further investigation in interferon‐free regimens in combination with direct‐acting antiviral agents.